Expressive Speech Acts in Pa'katia Verses at The Rambu Solo’ Ceremony of The Toraja Indigenous People - Anastasia Baan; Markus Deli Girik Allo; Jeklin Pabisa (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Pa'katia is taught from generation to generation orally so it is feared that its authenticity will fade by the influence of the current era of globalization and information, because at present time pa'katia has rarely been performed at funeral ceremonies, especially in the Sa'dan-Toraja area. Because of this problem at this time, many people do not know the existence of the dance, while the public knows it, but many people do not know the meaning and meaning conveyed in the pa'katia dance. The type of research used in this study is qualitative research. The data in this study describe expressive speech in pa'katia verses at the rambu solo’ ceremony for the sa’dan area of Toraja using a semiotic approach. The data of this study is in the form of utterances in the pa'katia verses at the rambu solo’ ceremony. The data in this study was sourced from informants, namely pa'katia actors, traditional leaders, and the Toraja community. The data collection techniques used are observation and interviews. The data analysis technique used by the author in this study was to identify the utterances in the pa'katia verses at the rambu solo’ ceremony of the Toraja community. Then analyze and describe the meaning of expressive speech in pa'katia verses and explain the results of the study. This research shows that expressive speech acts in pa'katia verses at the rambu solo’ ceremony of the Toraja indigenous people contain the meaning of application for permission, condolences, praise, hope, gratitude, apology, respect, heartache, request, disappointment, resignation, conviction, and togetherness.